2020
DOI: 10.1007/s10266-020-00522-y
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue failure load of immature anterior teeth: influence of different fiber post-core systems

Abstract: The aim was to explore the fracture-behavior, survival and marginal-microgaps within the root-canal of immature anterior teeth restored with different fiber-reinforced post-core composites (FRCs). 180 bovine-incisors were randomly divided into 6 groups (n = 30). One group served as control (group 6). The rest of the teeth were prepared to an internal diameter of 1.6 mm and the apex was sectioned. After application of an MTA-plug, teeth were restored with FRC materials: Group 1: Bioblock technique with short fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…Another major difference between the packable and flowable SFRC is that the flowable one contains 25 wt% of fibers, while in the packable variant this ratio is only 9 wt%. So far, flowable SFRC has yielded promising results when utilized in direct restorations in different clinical situations [ 16 , 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another major difference between the packable and flowable SFRC is that the flowable one contains 25 wt% of fibers, while in the packable variant this ratio is only 9 wt%. So far, flowable SFRC has yielded promising results when utilized in direct restorations in different clinical situations [ 16 , 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical testing was carried out in two phases. In the first phase, all restored specimens were submitted to an accelerated fatigue-testing protocol [ 16 , 17 ] by a hydraulic testing machine (Instron ElektroPlus E3000, Norwood, MA, USA) placed parallel to the long axis of the tooth. This phase served the purpose of simulating normal biting forces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operator also had to calculate the thickness of the shallowest layer of SFRC in the canal (4 mm), which left us with an approximately 6-mm-long FRC post for light transfer. As light transfer to the apically placed SFRC is a clinically important part of the Bioblock technique, it has been verified using the microhardness test in previous in vitro studies, which have clearly shown that SFRC can be appropriately cured in the canal with extended light-curing time (80 seconds) [ 15 31 ]. The authors would like to emphasize that in our studies and in this case, the SFRC was placed not more than 6–7 mm deep to the canal orifice, which seems to be a depth at which the setting and curing of SFRC can be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The fracture toughness and flexural strength of new short fiber-reinforced composite materials are similar to that of dentin's, therefore they behave as elastic materials (Lassila et al, 2018). Many studies have shown that better results can be obtained if short fiber-reinforced composite is used rather than conventional composite resin to substitute great amount of missing dentin (Fráter et al, 2019;Fráter et al, 2020;Forster et al, 2016). Furthermore the pattern of fracture is dominantly favorable when using fiber-reinforced composite, meaning the fibers first absorb, then dissipate and redirect the stress in the form of crack and/or fracture towards the surface of the tooth (…”
Section: Figure 6 Curve Showing a Fatal Unrepairable Fracture In Case Of Restored Teethmentioning
confidence: 99%